2021
DOI: 10.1097/olq.0000000000001376
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Online Sex Partners Among Gay, Bisexual and Other Men Who Have Sex With Men: Results From a National Survey

Abstract: Background: Associations between online sex seeking and increased risk for sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) among men who have sex with men (MSM) typically rely on convenience samples. We examined Internet and mobile app use for finding sex partners among a nationally representative sample of MSM. Methods:We analyzed 2011 to 2017 data from the National Survey of Family Growth, a nationally representative sample of the civilian, non-institutionalized US population (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…This finding is important given that some HIV care providers have negative perceptions of MSM who report online partner seeking, and who are assumed to engage in increased sexual risk behaviors, without acknowledgment that it may also be associated with protective behaviors [ 83 ]. This study’s findings and those of others [ 9 , 67 , 81 , 82 , 84 , 85 ] demonstrating the association of online partner seeking not only with sexual risk but also with protective behaviors is important to help HIV care providers understand the nuances of online partner seeking and thereby have more open conversations about online partner seeking with their clients. Past studies show equivocal results about the relationship between online partner seeking and condomless sex, with some studies among MSM from rural areas or large cities showing higher odds [ 30 , 31 , 86 , 87 ], whereas others report lower odds [ 10 - 12 ] or no associations [ 85 , 88 ].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This finding is important given that some HIV care providers have negative perceptions of MSM who report online partner seeking, and who are assumed to engage in increased sexual risk behaviors, without acknowledgment that it may also be associated with protective behaviors [ 83 ]. This study’s findings and those of others [ 9 , 67 , 81 , 82 , 84 , 85 ] demonstrating the association of online partner seeking not only with sexual risk but also with protective behaviors is important to help HIV care providers understand the nuances of online partner seeking and thereby have more open conversations about online partner seeking with their clients. Past studies show equivocal results about the relationship between online partner seeking and condomless sex, with some studies among MSM from rural areas or large cities showing higher odds [ 30 , 31 , 86 , 87 ], whereas others report lower odds [ 10 - 12 ] or no associations [ 85 , 88 ].…”
Section: Discussionsupporting
confidence: 53%
“…This study’s findings and those of others [ 9 , 67 , 81 , 82 , 84 , 85 ] demonstrating the association of online partner seeking not only with sexual risk but also with protective behaviors is important to help HIV care providers understand the nuances of online partner seeking and thereby have more open conversations about online partner seeking with their clients. Past studies show equivocal results about the relationship between online partner seeking and condomless sex, with some studies among MSM from rural areas or large cities showing higher odds [ 30 , 31 , 86 , 87 ], whereas others report lower odds [ 10 - 12 ] or no associations [ 85 , 88 ]. Our results revealed lower odds for online partner seeking among those who reported recent condomless insertive and receptive anal sex.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Numerous studies, as compiled in one meta-analysis, have explored HIV and sexually transmitted infection (STI) transmission risk among app-using MSM [8]. There is some evidence that MSM who use apps to meet partners are more likely to engage in condomless anal sex, have a higher number of sex partners and experience higher incidence of STIs, such as gonorrhea and chlamydia, as compared to those who meet partners in-person exclusively [9,10]. Other studies are more equivocal and have found that meeting partners online is not predictive of sexual risk behaviors [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis found that sexual encounters that were initiated online were more likely to have unprotected anal intercourse, whereas recent studies have found that app-users were more likely to have sexually transmitted infections (gonorrhea, chlamydia, and syphilis) [8][9][10]. In addition, though MSM who find their partners online are more likely to engage in risky behaviours, they are also more likely to have regular sexual risk assessments and treatment for sexually transmitted infections [11][12][13].…”
Section: Introductionmentioning
confidence: 99%